(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
This work, addressing the critical issues that have emerged two decades after the introduction of the Italian legislation on supported decision-making, seeks to critically reassess the “paternalistic” approach traditionally characterizing protective measures for individuals wholly or partially lacking autonomy. In this context, and in light of the multidimensional perspective of the United Nations Convention on the Rights of Persons with Disabilities – recently reflected in legislative reforms and in the jurisprudence of the Supreme Court and the European Court of Human Rights – the focus shifts to embracing the “uniqueness” of each individual in their complexity as the sole path to ensuring the effectiveness of protection.